Σύνθεση και παρουσίαση όπερας δωματίου "Στην Αλεξία" - (:unkn) unknown (My University, 2020)
«Στην Αλεξία» της Σοφίας Μπαρδούτσου. Όπερα δωματίου βασισμένη στο βιβλίο «Τον Καιρό του Βουλγαροκτόνου» της Πηνελόπης Δέλτα.

"For Alexia" by Sofia Bardoutsou. Chamber opera based on the book "In the Heroic Age of Basil II: Emperor of Byzantium" by Penelope Delta.
For Alexia- Chamber Opera
Keywords: Στην Αλεξία Όπερα δωματίου Σύνθεση για τις τέχνες της παράστασης Τον καιρό του Βουλγαροκτόνου- Πηνελόπη Δέλτα; For Alexia Chamber Opera Composition for theatre, cinema and perfoming arts In the Heroic Age of Basil II: Emperor of Byzantium Penelope Delta